Pengaruh Punishment Dan Reward Terhadap Kinerja Karyawan Pada PT. Gelatik Supra Kantor Cabang Medan - Amelia Yuliana; Sugito Sugito; Amrin Mulia (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2022)
This study aims to determine "The Influence of Punishment and Rewards on Employee Performance at PT. Gelatik Supra Medan Branch Office”. The type of data in this study is associative, which is a research that is asking the relationship between two variables. The population in this study were 40 contract employees. Data collection techniques in the form of distributing questionnaires to employees. The sample used in this study were contract employees of the operational and supporting divisions of PT. Gelatik Supra Medan Branch Office. Data processing was carried out using the SPSS version 21 application, with descriptive analysis and hypothesis testing of multiple linear analysis. The results of this study indicate that: (1) the punishment variable partially affects the performance of the employees of PT. Gelatik Supra Medan. (2) partially reward variables affect the performance of employees of PT. Gelatik Supra Medan. (3) Simultaneously punishment and reward have a positive and significant effect on the performance of employees of PT. Gelatik Supra Medan.